2016
DOI: 10.5897/ajar2015.9765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sowing dates and nitrogen levels for ethanol production from sweet sorghum stalks and grains

Abstract: Sweet sorghum is being investigated as a feedstock for ethanol production in semi-arid countries. It can be grown with fewer inputs than other energy crops. In Iran, due to long growing season, ethanol is produced from both sweet sorghum stem and grain. In other countries, ethanol is not produced from sweet sorghum grain due to low grain yield or short growing season. The purpose of this study was to maximize ethanol production from both stem and grain of sweet sorghum. Four planting dates (July 5, July 14, Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…These attributes have bestowed higher number of leaves per plant. Similar results were found by Abbas et al (2016) and Dixit et al (2005) where number of leaves per plant had significantly -1 increased by nitrogen levels from 40 to 180 kg N ha .…”
Section: Resultssupporting
confidence: 86%
“…These attributes have bestowed higher number of leaves per plant. Similar results were found by Abbas et al (2016) and Dixit et al (2005) where number of leaves per plant had significantly -1 increased by nitrogen levels from 40 to 180 kg N ha .…”
Section: Resultssupporting
confidence: 86%
“…The maximum total sugar (19.70%) was observed in 20 th October sown crop which was significantly higher than 5 th November sown crop. The findings were in close conformity with those of Almodares and Hoseini (2016) in sweet sorghum, as they reported that timely sown crop gave higher total sugar content as compared to late sown. It was observed that the spacing of 20 × 10 cm significantly affects the total sugar content and spacing of 20 × 7.5 cm and 20 × 5 cm were statistically at par with each other.…”
Section: Total Sugar (%) On Dry Weight Basissupporting
confidence: 84%
“…Sanghera et al (2016)reported that planting from 15th October to 30th October resulted in low pol (%) cane while 15 November planting showed promising results for enhancement of pol (%) cane. Abbas and Hossan (2015)observed that pol decreased from 12% to 6.71 % by delay in planting. Almodares and Darany (2006) also stated that higher pol (%) cane was recorded in early plantings.…”
Section: Effects Of Planting Datementioning
confidence: 99%